Barcelona Urban Futures - Cultural Pasts: Sustainable Cities, Cultures & Crafts -DIGITAL HERITAGE 2.3 - Mendes, P. (Urban Futures - Cultural Pasts: Sustainable Cities, Cultures & Crafts - AMPS, Universitat Politècnica de Catalunya, Barcelona, Spain, 2024)
Session chair on Congress Barcelona Urban Futures - Cultural Pasts: Sustainable Cities, Cultures & Crafts